Tricks in magic square / Chew Yee Ming, Ch’ng Pei Eng and Ng Kok Shien - Chew, Yee Ming (Unit Penerbitan dan Publisiti JSKM, 2022)
Have you tried to solve a magic square in less than five minutes? It’s fun and good for brain teaser activity. To engage students in learning mathematics and develop mathematical skills, the magic square can become one of the useful tools in recreational mathematics. This kind of logic puzzle provides an alternative to solve traditional arithmetic calculations in a playful and meaningful way. A magic square is a square of array positive integers where the sum of each row, column and diagonal is the same. One of the example 3 x 3 magic squares is shown in Figure 1. We can observe that the sum of each row, column and diagonals is 18. 18 is called a magic constant There is a trick to tackle the above magic square. Make sure that all nine numbers given are in consecutive order. Those nine numbers can be arranged in ascending or descending order. To calculate a magic constant, you need to add up all the nine consecutive numbers and divide by three. This example uses the numbers 2, 3, 4, 5, 6, 7, 8, 9, 10.